Gambaran pH Saliva pada Siswa-siswi Madrasah Tsanawiah di Tegalarum Klaten - Viliya Qodriyani Maryama; Dwi Suyatmi; Almujadi Almujadi (Journal of Oral Health Care, 2017)
Saliva is a viscous fluid produced by the salivary glands located under the tongue, cheek muscle area and the area near the ceiling degree of acidity (pH) is used to express the degree of acidity or alkalinity of a solution owned. Salivary pH 6.7 to 7.3 in a normal state. The main problem of dental health in Indonesia is the high prevalence of the hard tissues of the tooth and occurs mostly in children of school age poor oral hygienist. The purpose of this study to describe the pH of saliva on the students of Madrasah Tegalarum Tsanawiah in Klaten. The subjects of the research is 50 students of class VII and VIII. This study used survey method with quantitative descriptive research design, and the results are presented in tabular form and percentage terms. Results of research on students of Madrasah Tsanawiah in Tegalarum, Klaten that there is the influence of salivary pH by tooth brushing habits while bathing and brushing your teeth after breakfast as well as the use of herbal toothpaste and nonherbal. Getting the picture of the pH of saliva on the students of Madrasah Tsanawiah in Tegalarum, Klaten with the criteria of acidic, neutral and alkaline. The presence of saliva pH in Madrasah picture Tsanawiah acid Tegalarum criteria.